Predictions of middle-ear and passive cochlear mechanics using a finite element model of the pediatric ear - Wang, Xuelin (J Acoust Soc Am, 2016)
A finite element (FE) model was developed based on histological sections of a temporal bone of a 4-year-old child to simulate middle-ear and cochlear function in ears with normal hearing and otitis media. This pediatric model of the normal ear, consisting of an ear canal, middle ear, and spiral cochlea, was first validated with published energy absorbance (EA) measurements in young children with normal ears. The model was used to simulate EA in an ear with middle-ear effusion, whose results were compared to clinical EA measurements. The spiral cochlea component of the model was constructed under the assumption that the mechanics were passive. The FE model predicted middle-ear transfer functions between the ear canal and cochlea. Effects of ear structure and mechanical properties of soft tissues were compared in model predictions for the pediatric and adult ears. EA responses are predicted to differ between adult and pediatric ears due to differences in the stiffness and damping of soft tissues within the ear, and any residual geometrical differences between the adult ear and pediatric ear at age 4 years. The results have significance for predicting effects of otitis media in children.